Economic security in Southeast Asia: an introduction - Chong, Alan (2022)
The subject of economic security has always been bandied about in academic discourse since the emergence of an interconnected world economy. With ASEAN states getting increasingly enmeshed in free trade agreements, and common market like arrangements, it is imperative to explore what economic security means for national governments today. The shocks of the 2017-20 Donald Trump presidency of the USA and the COVID-19 pandemic impart timely momentum for inquiring after economic security. If the USA currently embodies the idea of zero-sum economic logics as the way forward into the twenty first century, it becomes even more urgent that Asians re-examine the degrees of openness needed to sustain growth and prosperity. Contributors to this Special Section will not only examine government-to-government trade interactions, the prospects of Islamic Finance and gender inequalities will also be analysed in terms of how they can make or break conventional notions of economic security.